1986
DOI: 10.1093/oxfordjournals.eurheartj.a062142
|View full text |Cite
|
Sign up to set email alerts
|

The haemodynamic effects of amrinone in patients with mitral stenosis and pulmonary hypertension

Abstract: The aim of this study was to investigate the haemodynamic effects of amrinone in patients with pulmonary hypertension and impaired right ventricular function. Twelve patients with mitral stenosis (NYHA classification III and IV) took part in the study. The haemodynamic measurements were performed in the steady state under anaesthesia prior to surgery. The patients received a bolus injection of 1.5 mg kg-1 amrinone; haemodynamic measurements were taken at 3, 5, 10, 15, 20 and 30 min. Amrinone increased cardiac … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The use of catecholamines is frequently associated with tachycardia or dysrhythmias, resulting in an imbalance in the myocardial oxygen supply/demand ratio [5]. Other phosphodiesterase inhibitors, such as amrinone [6] and milrinone [7], are also known to increase heart rate, and that is expected to result in increased myocardial oxygen consumption. In contrast, toborinone is known to have positive inotropic and vasodilating effects without increasing myocardial oxygen consumption [2].…”
Section: Discussionmentioning
confidence: 99%
“…The use of catecholamines is frequently associated with tachycardia or dysrhythmias, resulting in an imbalance in the myocardial oxygen supply/demand ratio [5]. Other phosphodiesterase inhibitors, such as amrinone [6] and milrinone [7], are also known to increase heart rate, and that is expected to result in increased myocardial oxygen consumption. In contrast, toborinone is known to have positive inotropic and vasodilating effects without increasing myocardial oxygen consumption [2].…”
Section: Discussionmentioning
confidence: 99%
“…As with obstructed TAPVR, therapies that decrease PVR increase pulmonary blood flow and may precipitate pulmonary edema without improving CO. Atz et al [48] evaluated iNO in children with PHTN due to congenital mitral stenosis and demonstrated significant reductions in PVR and pulmonary artery pressures; however, cardiac output remained unchanged. Hess et al [49] evaluated the effects of amrinone in 12 adult patients with mitral stenosis and RV dysfunction. The combined inotropic and vasodilating properties of amrinone produced significant reductions in PVR and pulmonary arterial pressures, as well as significant increases in CO. Aortic stenosis and coarctation of the aorta cause PHTN.…”
Section: Left-sided Obstructive Lesionsmentioning
confidence: 99%